ADAPTASI IMPLEMENTASI KURIKULUM OPERASIONAL SATUAN PENDIDIKAN (KOSP) DALAM PENGEMBANGAN MUTU PENDIDIKAN BERBASIS KEBUTUHAN LOKAL DI SMP IT IQRA STABAT - Ramadhani, Putri Suci; Chaniago, Nasrul Syakur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The School Operational Curriculum (Kurikulum Operasional Satuan Pendidikan/KOSP) enables schools to translate the national curriculum into learning that reflects student characteristics and local needs. This study describes KOSP adaptation at SMP IT IQRA Stabat, analyzes locally responsive quality development, and identifies supporting and inhibiting factors. A descriptive qualitative case study was conducted using observation, in-depth interviews, and document review with the principal, vice principal for curriculum, and teachers. Data were analyzed through reduction, display, and conclusion drawing, supported by triangulation and member checking. The findings show that adaptation proceeded through policy socialization, team formation, needs analysis, document development, review, and approval. Local responsiveness was expressed through Islamic values, Malay culture, practical skills, social activities, and Pancasila Student Profile projects. Implementation was supported by school leadership, teacher willingness to learn, education-office training and supervision, and parent-community participation. Constraints included uneven teacher understanding, administrative workload, limited facilities, transition difficulties, and differences in teacher readiness. Schools responded through staged training, peer discussion, curriculum-team assistance, independent learning, facility proposals, and coordination with supervisors. KOSP has strengthened contextual and character-oriented education, but further improvement requires systematic local-needs mapping, equitable professional development, simplified administration, adequate learning resources, and specific evaluation indicators.